Digital Premarital Health via KesCatin: Implementation Challenges in Pringsewu, Indonesia - Nelly Indrasari; Risneni Risneni; Amrina Octaviana; Eva Berliana; Nurlaila Nurlaila; Roslina (Journal of Public Health Sciences, 2026)
Stunting remains a major public health concern in Indonesia. Prevention during the premarital period is essential, as risk factors such as anemia, undernutrition, and early pregnancy (<20 years) are often established before conception. To address this, the Ministry of Health developed the KesCatin application as a digital innovation to enhance premarital reproductive health education and screening. This study aimed to explore the implementation process, challenges, and opportunities of the KesCatin application in improving digital-based premarital health services as part of stunting prevention efforts in Pringsewu District. A descriptive qualitative design was employed. Data were collected through four Focus Group Discussions (FGDs) involving 35 cross-sector program managers and in-depth interviews with 26 brides-to-be who had used KesCatin. Data were analyzed thematically following Braun and Clarke’s six-step framework, supported by source triangulation and member checking for validation. All 5,818 prospective brides registered in January–June 2024 received digital health screening and counseling via KesCatin. However, 3.2% were anemic (Hb <12 g/dL) and 1.8% had chronic energy deficiency (MUAC <23.5 cm). Thematic analysis identified three main themes: (1) strong cross-sector collaboration, (2) improved access to reproductive health information, and (3) barriers including poor internet connectivity, limited digital literacy, and absence of offline features. KesCatin has significant potential to strengthen premarital health services and support stunting prevention. To optimize its impact, offline access, user training, and continuous monitoring are recommended.